Influence of Internet Use on Commercial Health Insurance of Chinese Residents - Xu, Bao-Chang; Xu, Xiao-Ni; Zhao, Jin-Chun; Zhang, Meng (Frontiers in Public Health, 2022)
As a necessary supplement to social medical insurance, commercial health insurance is an important part of the Healthy China strategy. This study based on the Chinese General Social Survey (CGSS) data in 2017 uses the probit model to analyze and study the internal relationship between Internet use and commercial health insurance purchase of urban and rural residents. The research results show that the use of Internet significantly promoted commercial health insurance purchase of residents, and the promotion effect for rural residents apparently better than that among urban residents. In addition, social level of residents is improved for the use of Internet, which can promote commercial health insurance purchase. It provides an significant reference value for the effective integration of Internet use and commercial health insurance, and the high-quality development of the modern insurance industry.